Ophthalmology in Byzantium between the 4th and the 7th century - Bieganowski, Lech (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
The article presents the state of development of medicine and ophthalmology in Byzantium in the period between the 4th and the 7th century. It discusses the life and work of Oribasius, Alexander of Tralles, Aëtius from Amida and Paullus from Aegina. It underlines the contribution of Oribasius into the dissemination of knowledge of Galen’s works. It was this physician and Alexander of Tralles as well as Aëtius from Amida that did not recommend the surgical treatment of cataract (e. g. hypochyma). Paullus from Aegina was an exception in this respect as he provided a detailed description of couching of cataractous lens (e. g. hypochyma). His description is more detailed and precise than the one provided 600 years earlier by Celsus.